Induction of MHC Class I HLA-A2 promoter by dengue virus occurs at the NF kappa B binding domains of the Class I regulatory complex - Othman, S.; Abd Rahman, N.; Yusof, R. (2012)
Despite aggressive efforts in dengue research, the control of dengue diseases and discovery of therapeutics against them await complete elucidation of its complex immune-pathogenesis. Unlike many viruses that escape the host's immune responses by suppressing the major histocompatibility complex (MHC) Class I pathway, many Flaviviruses up-regulate the cell surface expression of MHC Class I complex. We recently reported MHC Class I HLA-A2 promoter activation by all serotypes of dengue virus (DV). The mechanism by which DV regulates this is further explored here in HepG2 human liver cell line. Using real-time PCR, evidence that, similar to infections by other Flaviviruses, DV infection has the ability to up-regulate the MHC Class I transcription and mRNA synthesis, is presented. The region responsive towards DV infection of all serotypes was mapped to the Class I Regulatory Complex (CRC) of the HLA-A2 promoter. Competition electrophoretic mobility shift assay (EMSA) with NF kappa B probe established the presence of specific DNA-protein complex in DV-infected nuclear extracts. Antibody-supershift assays identified the MHC Class I promoter activation by DV to occur through binding of p65/p50 heterodimers and p65 homodimers to kappa B1 and kappa B2 cis-acting elements, respectively, within the CRC, and not with the interferon consensus sequence (ICS). This study presents evidence of MHC Class I gene modulation by DV, hence providing a better understanding of dengue immune-pathogenesis that would consequently facilitate the discovery of antiviral therapeutics against dengue. (C) 2011 Elsevier B.V. All rights reserved.